Genetic variability and heritability for yield and associated traits of synthetically derived wheat population under normal and late planting condition (Zoo Botanica, 2025)
A set of five synthetic wheat lines were crossed with four well-adapted cultivars using a 5 × 4 Line × Tester scheme, during the Rabi 2021-22, resulting in the development of 20 F1 hybrids. These F1 hybrids along with their parental genotypes were evaluated in the Rabi 2022-23 at the University of Agriculture, Peshawar, Pakistan, to examine genetic variability, heritability estimates (broad- and narrow-sense) and expected selection responses for yield-related traits under two sowing conditions: normal planting (mid-November) and late planting (mid-December). Experiments were carried out in randomized complete design (RCBD) replicated three times. Broad-sense heritability values were generally higher under normal sowing compared to late planting. Narrow-sense heritability was notably greater for spike initiation and plant height under normal planting, whereas traits such as spikes per plant, spikelets per spike, 1000-grain weight, biological yield and grain yield exhibited moderate narrow-sense heritability under late sowing. In contrast, traits including spike initiation, plant height, spike length and grain yield adjudged low narrow-sense heritability in the late environment. The Expected genetic gains were consistently higher in normal planting as compared to late sowing with values recorded for days to spike initiation (3.70 vs. 0.25), plant height (3.62 vs. 0.17), spikes plant-1 (1.09 vs. 0.88), grains spike-1 (1.94 vs. 1.89), 1000 grains weight (1.62 vs. 1.12), biological yield (4.67 vs. 2.82) and grain yield (1.88 vs. 0.27). The prime objective of this study was to select the best genotypes considering high broad sense heritability to proceed further for the varietal selection and use as a parent in local hybridization scheme.
Keywords: Synthetic wheat; genetic variability; heritability; yield associated traits; normal and late planting condition